Paul’s Transformation Leadership Behavior in the Letter to Titus - Harwanto, Budi (Klabat Theological Review; Vol 3 No 1 (2022): Klabat Theological Review, 2022)
Leadership is an essential tool to fulfill the objectives of church ministry and mission. Among several leadership styles, transformation leadership behavior is one of effective model to be implemented in the church. Since most of the transformational leadership discussion has focused secular organization context, it needs to construct a biblical foundation and its implication for the church organization setting. This study applies both theoretical review and biblical analysis that based on the Paul’s letter to Titus. The review of literature shows that theories on transformational leadership supports the characteristics of Paul’s leadership style. Paul develops a personal connection with Titus and this presents transformational leadership principles. Paul displays individual consideration by considering Titus as his true son in faith and as a vital co-worker instead of a general follower. Although Titus has some weaknesses as a young leader, the influence of his mentor encourages him to do his leadership tasks.  Moreover, Paul inspired Titus to be a faithful minister of God. He motivated him with a clear vision of the ministry by providing a good church leadership to face challenges. The blessed hope of eternal life became a great encouragement for Titus in dealing with critical situations. Finally, Paul stimulated Titus to teach the Cretan congregation true sound doctrine.  Through intellectual stimulation, Titus is encouraged to study the word of God carefully and apply it. Consequently, by applying the model of Paul’s leadership, Titus was being productive leader to the Cretan community of faith. Thus, an application in church arena helps the church progressively conform to Christ’s image. Church leaders’ behavior motivates church members to consistently grow in church community. Keywords : transformational leadership, Paul, Titus.   Bibliography Adams, Anthony Wayne. Shepherd leadership of Church of God pastors and how this relates to ministerial effectiveness (Doctoral dissertation). Available from ProQuest Dissertations and Theses database. (UMI No. 3570373), 2013. Banks, Robert J. & Ledbetter, Bernice M. Reviewing leadership: A Christian evaluation of current approaches. Grand Rapids, MI: Baker, 2016. Barbuto, John E. Jr., & Wheeler, Daniel W. Scale development and construct clarification of servant leadership . Group & Organization Management, 31 (3), 300-326. doi:10.1177/1059601106287091, 2006, 302. Bass, Bernard M. Leadership and performance beyond expectations . New York, NY: Free, 1985. Bell,  Skip. A time to serve: Church leadership for the 21 st century . Lincoln, NE: Advent Source, 2003. Blackaby, Henry T. & Blackaby, Richard. Spiritual leadership: Moving people on to God’s agenda , Nashville, TN: B&H, 2001. Burns, James M. Leadership . New York, NY: Harper & Row, 1978. Çoğaltay, Nazim. Conceptual perspectives on leadership. In E. Karadăg (Ed.), Leadership and organizational outcomes: Meta-analysis of empirical studies (pp. 1-18). doi:10.1007/978-3-319-14908-0_1, 2015. Covey, Stephen R. The 8th habit: From effectiveness to greatness . New York, NY: Free, 2004. Doukhan, Jacques B. The creation narrative. In S. Bell (Ed.), Servants & friends: Biblical theology of leadership (pp. 31-47). Berrien Springs, MI: Andrews University, 2014. Elliston, Edgar J. Leadership theory. In A. S. Moreau, H. Netland, & C. van Engen (Eds.), Evangelical dictionary of world missions (pp. 567-568). Grand Rapids, MI: Baker, 2000. George, Jennifer and Jones, Gareth. Understanding and managing organizational behavior (6th ed.) . Upper Saddle River, NJ: Pearson Prentice Hall, 2012. Harwanto, Budi. The mediating role of disciple-making process in the relationship of transformational leadership behavior, church ministry programs, and church membership retention (Doctoral dissertations). Adventist International Institute of Advanced Studies, Silang Cavite, Philippines, 2016. Kouzes, James M. & Posner, Barry Z. Leadership is a relationship. In J. M. Kouzes &  B. Z. Posner (Eds.), Christian reflections on the leadership challenge (pp. 119-126). San Francisco, CA: Jossey-Bass, 2004. Lea, Thomas D. & Griffin, Hayne P. 1, 2 Timothy, Titus: The New American commentar y. Nashville, TN: Broadman, 1992. Liefeld, Walter L. 1 & 2 Timothy/Titus: The NIV Application Commentary . Grand Rapids, MI: Zondervan, 1999. Malphurs, Aubrey & Mancini, Will. Building Leaders: Blueprints for Developing Leadership at Every Level of Your Church . Grand Rapids, MI: Baker, 2004. McConnel, Douglas. Leadership. In A. S. Moreau, H. Netland, & C. van Engen (Eds.), Evangelical dictionary of world missions (pp. 565-567). Grand Rapids, MI: Baker, 2000. Mounce, William D. Pastoral Epistles. In R. P. Martin (Ed.), Word Biblical Bommentary (Vol. 46, pp. 1-786). Nashville, TN: Thomas Nelson, 2000. Northouse, Peter G. Leadership: Theory and practice (5th ed.). Thousand Oaks, CA: Sage, 2021. Schermerhorn Jr, John R., Hunt, James G., Osborn, Richard N., & Uhl-Bien, Mary. Organizational behavior (11th ed.). Hoboken, NJ: Wiley, 2010. Scuderi, Noelle F. Servant leadership and transformational leadership in church organizations (Doctoral dissertation). Available from ProQuest Dissertations and Theses database. (UMI No. 3413541), 2010. Srithongrung, Arwiphawee. The causal relationships among transformational leadership, organizational commitment, and employee effectiveness. International Journal of Public Administration, 34 (6), 376-388. doi:10.1080/01900692.2011.569917, 2011. Stowell, Joseph M. Shepherding the church: Effective spiritual leadership in a changing culture. ( Chicago, IL: Moody Press, 1997. Tilstra, Doug, Peter: A narrative of transformation. In S. Bell (Ed.), Servants & friends: Biblical theology of leadership (pp. 291-307). Berrien Springs, MI: Andrews University, 2014. Treston, Kevin. Creative Christian leadership: Skill for more effective ministry , Mystic, CT: Twenty-Third, 1995. Whiterington III, Ben. Letters and homilies for Hellenized Christian: A socio-rhetorical commentary on Titus, 1-2 Timothy, and 1-3 John (Vol. 1). Downers Grove, IL: InterVarsity, 2006.